Long-Term Effects of a Novel Continuous Remote Care Intervention Including Nutritional Ketosis for the Management of Type 2 Diabetes: A 2-Year Non-randomized Clinical Trial - Athinarayanan, Shaminie J.; Adams, Rebecca N.; Hallberg, Sarah J.; McKenzie, Amy L.; Bhanpuri, Nasir H.; Campbell, Wayne W.; Volek, Jeff S.; Phinney, Stephen D.; McCarter, James P. (Frontiers in Endocrinology, 2019)
Purpose: Studies on long-term sustainability of low-carbohydrate approaches to treat diabetes are limited. We previously reported the effectiveness of a novel digitally-monitored continuous care intervention (CCI) including nutritional ketosis in improving weight, glycemic outcomes, lipid, and liver marker changes at 1 year. Here, we assess the effects of the CCI at 2 years. Materials and methods: An open label, non-randomized, controlled study with 262 and 87 participants with T2D were enrolled in the CCI and usual care (UC) groups, respectively. Primary outcomes were retention, glycemic control, and weight changes at 2 years. Secondary outcomes included changes in body composition, liver, cardiovascular, kidney, thyroid and inflammatory markers; diabetes medication use and disease status. Results: Significant changes from baseline to 2 years in the CCI group included: HbA1c (-12% from 7.7±0.1%); fasting glucose (-18% from 163.7±3.9 mg/dL); fasting insulin (-42% from 27.7±1.3 mIU L-1); weight (-10% from 114.56±0.60 kg); systolic blood pressure (-4% from 131.7±0.9 mmHg); diastolic blood pressure (-4% from 81.8±0.5 mmHg); triglycerides (-22% from 197.2±9.1 mg/dL); HDL-C (+19% from 41.8±0.9 mg/dL), and liver alanine transaminase (-21% from 29.16±0.97 U/L). Spine bone mineral density in the CCI group was unchanged. Glycemic control medication use (excluding metformin) among CCI participants declined (from 55.7% to 26.8%, P=1.3x10-11) including prescribed insulin (-62%) and sulfonylureas (-100%). The UC group had no significant changes in these parameters (except uric acid and anion gap) or diabetes medication use. There was also significant resolution of diabetes (reversal, 53.5%; remission, 17.6%) in the CCI group but not in UC. All the reported improvements had p-values <0.00012. Conclusion: The CCI group sustained long-term beneficial effects on multiple clinical markers of diabetes and cardiometabolic health at 2 years while utilizing less medication. The intervention was also effective in the resolution of diabetes and visceral obesity with no adverse effect on bone health.